A History of Mathematical Sciences in Nepal - Jha, K.; Adhikary, P.R.; Pant, S.R. (Kathmandu University Journal of Science, Engineering and Technology, 2006)
The history of teaching mathematics is as old as human civilization. The history of mathematics is a powerful tool for disseminating an understanding of mathematics. The history of mathematics teaching in Nepal started with the establishment of "Gurukula" in ancient times, while the modern education system in Nepal appears to follow the global educational trends. The aim of this paper is to present a brief historical account of Nepalese mathematicians up to the nineteenth century and their notable contributions to mathematical sciences in Nepal.